Mild Uncoupling of Oxidative Phosphorylation and Prospects of Its Use in Medicine (Review) - Zagoskin, Pavel P.; Erlykina, Elena I. (British Journal of Healthcare and Medical Research, 2022)
The review summarizes and analyzes modern data about the structure and mechanism of action of endogenous and exogenous substances that have been able to uncouple softly oxidative phosphorylation from respiration in mitochondria of various body tissues. The data on the effect of mild uncouplers on the redistribution of hydrogen ions on both sides of the inner mitochondrial membrane and the value of the proton membrane potential are systematized. Evidence of a decrease in the level of reactive oxygen species under the action of these substances is given. Typical physiological effects that develop as a result of the action of mild uncouplers (thermogenesis, prevention of mito- and apoptosis) are described. Possible ways of using these substances as drugs for the prevention and treatment of obesity, cardiovascular, neurodegenerative, inflammatory and oncological diseases are discussed.